Pressure–temperature–time–composition (P–T–t–x) of paleo–fluid in Permian organic–rich shale of Lower Yangtze Platform, China: Insights from fluid inclusions in fracture cements. (April 2021) - Huang, Yahao; He, Sheng; Guo, Xiaowen; Wu, Zhongrui; Zhai, Gangyi; Huang, Zhengqing; Zhang, Min; Xiao, Qilin
Abstract: Recently, much attention has been paid to Permian shale from the Yangtze Platform because of the high–quality hydrocarbon source rock. This research investigates fracture veins derived from conventional cores of the Permian Leping Formation in the Pingle Depression, Lower Yangtze Platform. Based on petrographic observations, micro–Raman spectroscopy, and fluorescent spectrometry, hybrid CH4 –C2 H6 gas inclusions, pure CH4 inclusions, dissolved CH4 aqueous inclusions, and different abundant blue-green fluorescence petroleum inclusions were discovered in quartz and calcite. The pressure–temperature–time–composition properties of the CH4 –bearing inclusions were obtained by quantitative Raman analysis and thermodynamic models. The pore fluid pressure (59.05–87.78 MPa) calculated from Raman shift of C–H symmetric stretching ( v 1 ) band of methane indicates inclusions trapped at close to lithostatic pressures, which can provide a key evidence for understanding the formation and evolution of overpressure. PT entrapment conditions, reconstruction of hydrocarbon generation and simulation of burial history permit to constrain accumulation time sequence of paleo-fluid in shale veins. Blue-green fluorescence with high-mature petroleum fluid trapped in late Cretaceous (~81–71 Ma); hybrid CH4 –C2 H6 fluid trapped in early Paleogene (~68–61 Ma); and CH4 fluid trapped in Paleogene (~62–51 Ma). Dry gas generation period close to the age of maximum burial depth at early Himalayan uplift period. Highlights: Quartz and calcite cements were found in near-horizontal and high-angle Permian shale veins. Raman quantitative analysis recovery paleo-pressure of CH4 -bearing inclusions. Hydrocarbon-generating pressurization caused overpressure state. Distinction of different components fluid charging time in fracture veins.